2013
DOI: 10.1016/j.biomaterials.2013.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-decellularized pancreas as a natural 3D scaffold for pancreatic tissue and whole organ engineering

Abstract: Approximately 285 million people worldwide suffer from diabetes, with insulin supplementation as the most common treatment measure. Regenerative medicine approaches such as a bioengineered pancreas has been proposed as potential therapeutic alternatives. A bioengineered pancreas will benefit from the development of a bioscaffold that supports and enhances cellular function and tissue development. Perfusion-decellularized organs are a likely candidate for use in such scaffolds since they mimic compositional, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(256 citation statements)
references
References 65 publications
9
237
0
10
Order By: Relevance
“…3). Similar data have been recently produced in a rodent model (136). However, the successful decellularization and subsequent recellularization of the human pancreatic ECM has not been reported in the bioengineering literature.…”
Section: Ecm and Endocrine Pancreas Bioengineeringsupporting
confidence: 71%
“…3). Similar data have been recently produced in a rodent model (136). However, the successful decellularization and subsequent recellularization of the human pancreatic ECM has not been reported in the bioengineering literature.…”
Section: Ecm and Endocrine Pancreas Bioengineeringsupporting
confidence: 71%
“…70,71 A recent study of decellularized mouse pancreas identified several proteins present in the basement membrane, among them collagens I, III, V, and VI; laminins-111, 211, and 511; nidogens; and proteoglycans. 72 However, the exact role of specific ECM molecules in maintaining islet function is still under investigation. Table 1 summarizes key findings for different ECM molecules and their effect on various insulinproducing cell types.…”
Section: Ecm Cuesmentioning
confidence: 99%
“…64,65 This technology used to engineer lungs, 66 tissue grafts for heart, 67 liver 68 and pancreas in vitr. 69 Decellularization is also used in intestinal, renal and, cardiac, hepatic, skin tissue engineering ( Figure 5). …”
Section: De-cellularizationmentioning
confidence: 99%